2021
DOI: 10.1021/acsapm.1c01275
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Rheology, and Assessment of 3D Printability of Multifunctional Polyesters for Extrusion-Based Direct-Write 3D Printing

Abstract: Three-dimensional (3D) printing offers the unprecedented ability to create medical devices with complex architectures matched to the patient’s anatomy. However, the development of 3D printable synthetic polymers for biomedical applications has been relatively slow. Here, we present the synthesis and characterization of a library of single-component, undiluted, modular multifunctional polyesters for extrusion-based direct-write 3D printing (EDP). The polyesters were synthesized using carbodiimide-mediated polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Therefore, the vitrimer has a higher shear-thinning dependency, which is usually desirable in extrusion-based 3D-printing processes. Higher shear thinning is usually desired for two reasons: (1) the polymer extruded through the nozzle (high shear rate) should have high flowability, which translates into low viscosity values; and (2) during the deposition step (low shear rate), the polymer should have high viscosity to hold its shape under gravity and under the layers on top [ 7 , 38 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the vitrimer has a higher shear-thinning dependency, which is usually desirable in extrusion-based 3D-printing processes. Higher shear thinning is usually desired for two reasons: (1) the polymer extruded through the nozzle (high shear rate) should have high flowability, which translates into low viscosity values; and (2) during the deposition step (low shear rate), the polymer should have high viscosity to hold its shape under gravity and under the layers on top [ 7 , 38 ]. …”
Section: Resultsmentioning
confidence: 99%
“…At the same time, viscosity drops after the T v ; where the covalent exchanges have commenced and sudden drop of viscosity denotes the transition flow from William‐Landel‐Ferry to Arrhenius equation 66,74 . Also, rheological studies exhibited tan delta values determine the material deformation; and the reported vitrimer exhibits tan delta values have described the material is flexible and good to perform the printing 75 . Altogether, vitrimers displaying high‐yield strength, low viscoelasticity at high temperature and lower tan delta values are supporting that the material can effectively utilized via 3D‐printing techniques, and making suitable for an engineering application.…”
Section: Rheology Vitrimer Inksmentioning
confidence: 97%
“…One the most commonly used 3D printing techniques for tissue engineering applications is extrusion-based direct-write printing. [63][64][65][66][67] This technique goes by several other names, including robotic dispensing, continuous ink writing, direct-write plotting, or solid freeform fabrication. [68] In this technique, a polymer ink is dispensed through a nozzle using pneumatic pressure, a pneumatic actuator, or a mechanical screw.…”
Section: D Printingmentioning
confidence: 99%